2022
DOI: 10.1371/journal.pone.0272976
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of workplace safety climate among power sector employees: A comparative study of cross-culture employer in Pakistan

Abstract: Pakistan’s power sector has undergone extensive reforms to improve its technical and monetary performance over the last two decades. However, despite its fast-growing and hazardous nature, safety research remains limited in this context. This study aims to address this gap by assessing the level of safety climate in the power sector and comparing the safety climate in plants operated by multinational companies (MNCs) and local companies (LCs).To this end, five power plants operating in the southern part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The finding from this study supports the research hypothesis, that cultural diversities tend to affect organizational factors in oil and gas companies. Arooj et al [16] also observed that the management of multinational power companies in Pakistan had a higher level of management commitment to safety than the local companies. A high level of management commitment to safety has been shown to foster more willingness by the employee to report safety issues, better team collaboration, and more efficient supervision from the safety supervisors and line manager [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding from this study supports the research hypothesis, that cultural diversities tend to affect organizational factors in oil and gas companies. Arooj et al [16] also observed that the management of multinational power companies in Pakistan had a higher level of management commitment to safety than the local companies. A high level of management commitment to safety has been shown to foster more willingness by the employee to report safety issues, better team collaboration, and more efficient supervision from the safety supervisors and line manager [17].…”
Section: Discussionmentioning
confidence: 99%
“…The result gives an indication that workers in multinational companies are given more decision latitude when carrying out their task. Arooj et al [16] reported that multinational companies provided more management safety empowerment to their workers than local companies. Several studies have shown that higher decision latitude increases job satisfaction, improves performance, and enhances creativity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation